Os impactos fiscais indiretos das operações compromissadas: uma análise via ARDL - Lacerda, Caio Eduardo Botelho (2022)
This paper analyzes the indirect fiscal impacts of the repurchase agreements in the period from December 2006 to March 2022. These impacts are estimated using the ARDL model applied to cointegration. Repurchase agreements’ direct fiscal impact is known, as it is calculated in the statistics of the Central Bank of Brazil. However, the indirect fiscal effects of repurchase agreements have not been investigated yet. This article examines them, particularly in the average cost of debt. The results of the estimation report that the repurchase operations were statistically significant to the average cost of the federal public debt, in the short and long-term. Repurchase agreements change the size of the debt and modify the base on which the interest charged on the federal securities debt are paid – this is the base-effect; They also increase the debt stock and change the risk perception that agents bear about the debt; thus, the public debt buyers requested different interest rates to purchase federal public bonds. This is the risk-effect.